THE RELATION BETWEEN HUMAN, UNIVERSE AND GOD IN AHMAD FUADI’S NOVEL ANAK RANTAU - Nahdhiyah Nahdhiyah (Elite : English and Literature Journal, 2018)
Abstract            The nature of literature is beautiful and meaningful or in the other word is beautiful and teaching something. Studying literature is not only elaborating the beautiful string of word, sentence as the structure building of literary work. As the nature of literature, then, studying literature must touch into the revelation meaning beyond the text, revealing values, moral messages in literary work so the function of literature which is not mere giving pleasure  and entertaining. This study reveals relation between human, universe, and God portrayed in novel “Anak Rantau” by Ahmad Fuadi. This study analyzes texts using hermeneutic method. The relation between human, universe, and God means is how human supposed to behave toward universe which suits to the purpose of the human creation as “khalifah”  in the earth. The portrait of relation between human, universe,and God seems in some story extracts. The effort to return the seaside condition and environment in large which polluted by poison and fish bones in “gotongroyong” to clean seaside for returning the seaside function as giving benefit to human. In addition, the relation between human, universe, and God seems when universe becomes a teacher for human which alwaays obeys to the God decision. Keywords: the nature of literature, khalifah, human, universe, God Abstrak            Hakikat sastra adalah indah dan bermakna atau dengan kata lain indah dan mengajarkan sesuatu. Mengkaji sastra tidak cukup hanya mengurai keindahan rangkaian kata, kalimat sebagai unsur pembangun sebuah karya sastra. Sesuai dengan hakikatnya, maka Mengkaji sastra haruslah sampai pada mengungkap makna di balik teks, mengungkap nilai-nilai, pesan-pesan moral yang terkandung dalam sebuah karya sastra sehingga fungsi sastra yang tidak hanya sekedar memberi kesenangan dan menghibur semata bisa terungkap. Kajian ini mengungkap hubungan antara manusia, alam, dan Tuhan yang tergambar pada novel Anak Rantau karya Ahmad Fuadi.  Kajian ini menganalisis teks dari penggalan konflik dengan metode hermenutika. Hubungan antara manusia, alam dan Tuhan yang dimaksudkan adalah bagaimana seharusnya manusia berperilaku terhadap alam sesuai dengan tujuan penciptaannya sebagai khalifah di bumi. Potret hubungan antara manusia, alam dan Tuhan nampak pada beberapa penggalan cerita. Adanya upaya mengembalikan kondisi pantai dan lingkungan secara luas yang tercemar oleh racun dan bangkai-bangkai ikan dengan cara bergotongroyong menbersihkan pantai untuk mengembalikan fungsi pantai yakni memberi manfaat kepada manusia. Selain itu hubungan manusia, alam, dan Tuhan juga nampak ketika alam dijadikan guru oleh manusia yang selalu patuh pada hukum-hukum  Tuhan. Kata kunci: Hakikat sastra, khalifah, manusia, Alam, Tuhan